SERP: secure energy-efficient routing protocol for densely deployed wireless sensor networks - Pathan, Al-Sakib Khan; Hong, Choong Seon (Springer, 2008)
In this paper, we present secure energy-efficient routing protocol (SERP) for densely deployed wireless sensor networks which aims to achieve robust security for transmitted sensor readings with an energy-efficient network backbone. When the sensors with limited energy budgets are deployed in hazardous environment, ensuring energy efficiency and security of the sensor readings becomes a crucial task. Here, we address how to deal with such a deployment scenario. Our protocol ensures secure transmission of data from the source sensors to the base station in a way that it can best utilize the available amount of energy in the network. We use one-way hash chain and pre-stored shared secret keys for ensuring data transmission security. In SERP, first, a sink rooted tree structure is created as the backbone of the network. This energyefficient network structure is used for authenticated and encrypted data delivery from the source sensors to the base station. To introduce data freshness, SERP includes an optional key refreshment mechanism which could be applied depending on the application at hand. Our analysis and simulation results show that SERP provides a good level of confidentiality and authenticity of data that are transmitted from the sensors to the base station. It also helps for energy-efficient structuring of the network so that the maximum lifetime of the network could be achieved.